2021
DOI: 10.3389/fnins.2021.755327
|View full text |Cite
|
Sign up to set email alerts
|

Turbo Gradient and Spin Echo PROPELLER-Diffusion Weighted Imaging for Orbital Tumors: A Comparative Study With Readout-Segmented Echo-Planar Imaging

Abstract: Purpose: To qualitatively and quantitatively compare the image quality and diagnostic performance of turbo gradient and spin echo PROPELLER diffusion-weighted imaging (TGSE-PROPELLER-DWI) vs. readout-segmented echo-planar imaging (rs-EPI) in the evaluation of orbital tumors.Materials and Methods: A total of 43 patients with suspected orbital tumors were enrolled to perform the two DWIs with comparable spatial resolution on 3T. The overall image qualities, geometric distortions, susceptibility artifacts, and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Several studies have used TGSE-BLADE DWI to reduce geometric distortion and susceptibility artifact in regions where strong magnetic susceptibility presents 20 , 24 26 . However, it remains unknown whether TGSE-BLADE DWI can reduce clip-induced artifact and improve image quality in patients who have undergone cerebral aneurysm clipping.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used TGSE-BLADE DWI to reduce geometric distortion and susceptibility artifact in regions where strong magnetic susceptibility presents 20 , 24 26 . However, it remains unknown whether TGSE-BLADE DWI can reduce clip-induced artifact and improve image quality in patients who have undergone cerebral aneurysm clipping.…”
Section: Introductionmentioning
confidence: 99%
“…Readout-segmented echo-planar imaging (RESOLVE) has been proposed to signi cantly reduce image distortion and improve the image signal-to-noise ratio of diffusion-weighted imaging (DWI) and apparent diffusion coe cient (ADC) in head and neck small lesions by reducing the echo interval [19,20]. Histogram analysis and texture analysis based on RESOLVE ADC have been used for noninvasive assessment of tumor response after neoadjuvant chemoradiotherapy (CRT) in locally advanced rectal cancer [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al used radiomics features of targeted LNs based on multi-objective T2W images to predict LNM and reached an AUC of 0.92, with sensitivity of 89.8% and speci city of 82.3%[18]. Several previous studies have demonstrated that the sequence of RESOLVE could signi cantly reduce image distortion and improve the image quality by reducing the echo interval[19,20]. This high-resolution sequence has thinner slice thickness and higher image signal-to-noise ratio compared to conventional DWI, which may be bene cial in accurately delineating the high-signal area of primary tumor, while locating and detecting pathologically con rmed LNs node by node.…”
mentioning
confidence: 99%
“…Recently, TGSE BLADE DWI was shown to significantly reduce distortion, blurring, and magnetic-sensitive artifacts (10). This technique has been used to visualize orbital tumors, cerebellopontine angle tumors, and sinonasal lesions on 3T magnetic resonance images (MRI) (11–13). Recently, it has been confirmed that TGSE BLADE DWI possesses superior image quality in cholesteatoma imaging and may have a unique role in identifying particularly small cholesteatomas (14).…”
mentioning
confidence: 99%